Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VIII SMP Negeri 18 Padang - SRI WAHYUNI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication skills are one of the goals of mathematics learning that must be achieved by students. But learning activities in schools have not been optimal in facilitating students to improve their mathematical communication skills. One effort to overcome these problems is to apply the cooperative learning model Think Talk Write type. The purpose of this study is to describe whether the mathematical communication skills of students who learn by using cooperative learning models Think Think Write type are better than mathematical communication skills of students who learn by direct learning and describe the development of mathematical communication skills of students during the implementation of cooperative learning models of Think Think type Talk Write. This type of research is quasi-experimental and descriptive research design with Randomized Control Group Only Design. Based on the results of data analysis, it was concluded that the mathematical communication skills of students who learn using the Cooperative learning model Think Talk Write type is better than the mathematical communication skills of students who learn by direct learning in class VIII SMP Negeri 18 Padang. Then, the development of students' mathematical communication skills during the cooperative learning model applied to Think Talk Write type has increased. Keywords – Mathematical Communication Skills, Think Talk Write Cooperative Learning Model, Direct                    Learning